Pengaruh Pemasaran Media Sosial dan Kualitas Layanan Terhadap Keputusan Pembelian Jasa Fotografi F11 di Kecamatan Tanjung Morawa - Rahayu, Ajeng; Sabrina, Hesti; Nasution, Amrin Mulia Utama (Mahesa Research Center, 2024)
The purpose of this study was to determine the effect of Social Media Marketing and Service Quality on Purchasing Decisions for F11 Photography Services in Tanjung Morawa District. This research is associative research. The population in this study is the total data of 216 respondents of F11 Photograpy Service users, the calculation of the number of samples using the slovin formula with a sample size of 68 respondents. The data collection methods in this study were questionnaires, interviews and literature studies. The data analysis method uses descriptive methods and multiple linear regression analysis with a significant level of 0.05. The F test results show that service quality and service innovation together have a positive and significant influence on the dependent variable, namely purchasing decisions. Based on the test of the coefficient of determination (R2) shows that the Adjusted R Square value is 0.86%, meaning that social media marketing and service quality affect purchasing decisions by 86% and the remaining 14% can be explained by other factors not examined in this study